Q. 7 A3.8( 45 Votes )

For some constant

Answer :

Let f(x) = (x – a)(x – b)


f(x) = x2 – (a + b)x + ab




Since,


f’(x) = 2x – (a + b) + 0


= 2x – a – b


f’(x) = 2x – a – b


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar